Ground Water Quality Assessment of Different Villages of Chikkamagalur Block in Chikkamagalur District of Karnataka - K.R. Bindu, D. Sai Pavan; R.N. Meena, H.E. Sachin, Y.V. Singh* (Journal of the Indian Society of Soil Science, 2021)
Quality of the irrigation water is one of the important aspects for plant growth and it has been a major global concern in developing and developed countries. There has been a regular increase in the irrigated area in the country in the last decade that led to a higher yield potential. If poor quality of irrigation water is used it results in decreased yield. So there is a need to assess quality of the irrigation water before its use on the crops. An attempt was made to assess the ground water quality of different villages in Chikkamagalur block of Chikkamagalur district in Karnataka using various water quality parameters. The values of pH ranged from 6.3 to 8.0, while electrical conductivity ranged from 0.10 to 1.10 dS m-1. Sodium and potassium content in the irrigation water ranged from 0.13 to 3.83 and 0.10 to 5.12 meq L-1, respectively. Calcium and magnesium contents which indicate the hardness of the water and are the important cations was recorded between 0.60 and 5.85 meq L-1. Chloride concentration varied from 4.40 to 11.2 meq L-1, while bicarbonate ranged from 0.4 to 8.8 meq L-1. Based on irrigation water quality index (IWQI), it was found that 87.5% of the water samples of the study area was poor in quality and slightly unsustainable for irrigation, while 8.3% was very poor and only 4.2% was good in quality for irrigation.